In Tharaka South, Eastern Kenya, Socio-Economic Variables Influence the Use of Rainwater Collecting and Conservation Methods (International Journal of Innovative Research in Computer Science & Technology, 2021)
Rainwater harvesting and conserving  technologies are essential interventions for water supply  and food production in Kenya's dry and semi-arid regions  due to low soil moisture levels. Despite extensive study  on the subject, variables influencing farmer acceptance  and adaptation of these helpful technologies remain  unknown, and low adoption and adaption levels of these  beneficial technologies remain a problem. This study  expands on this feature, focusing on the Tharaka South  sub-county, where family food insecurity is exacerbated  by water shortage, unpredictable rainfall, and soil water  stress. A cross-sectional survey methodology was used to  gather farm and social data from 351 household heads.  Descriptive statistics and logistic regression were used to  analyze the data. Trashlines (73 percent) used in situ  rainwater collecting and saving methods more than  micro-catchments (26 percent), Zai pits (26 percent), and  Negarims (13 percent). Household size (p 0.01) and Zai  pit training (p 0.002) were positively and substantially  related with Zai pit usage, whereas overall farm size (p  0.01) and land tenure (p 0.01) had negative co-efficients.  Rainwater collection and conservation technologies were  disseminated using both official and informal teaching  methods. Farmers' age, family size, farm size, farming  history, training, and formal education were shown to be  significant variables influencing the adoption of rainwater  collecting and saving technology in Tharaka sub-county,  according to the research. In contrast to less resource intensive technologies, specific methods are required to  increase the efficiency of asset technology.
Keywords: Agriculture Climate Change; Dry Land; Economic; Rain Water Harvesting; Resource-Intensive